The Challenges of Romanian Higher Education – A Review on the Key Enablers for Modernization. (2016) - Fleacă, Elena; Marin, Alexandru; Fleacă, Bogdan
Abstract: In the boundaries of the European Union, education has a social dimension especially in an environment where skills and competences are acquired and refined through higher education. The paper aims to review the major challenges facing the sector of higher education at European Union level and to examine and summarize the key national responses/measures foreseen to address common national bottlenecks with respect to tertiary education: access, retention, and employability of students. The findings attempt to fill the knowing gap by systematically analyze the country statistical data and the key initiatives in developing human capital that help to transform the current higher education capacity towards more knowledge-based and innovative structure.